INFLUENCE OF UREA AND CHICKEN MANURE ON PRODUCING NEW PLANTS AND VEGETATIVE GROWTH OF STRAWBERRY (Fragaria x ananassa Duch) “DARSELECT” PLANTS - BARWARY, NAJI ISAM (Journal of Duhok University, 2021)
This study was performed during November 2020 to August 2021, in a private farm at Tishambik village, Kanimasi distract, Duhok, Kurdistan region / Iraq on strawberry plants Darselect cultivar to find out the effects of four levels of soil application urea (0, 1, 1.5 and 2 g plant-1) and three levels of chicken manure (0, 100 and 200 g plant-1) on producing new plants and vegetative growth of strawberry plants. General obtained results showed that the incremental application of urea and chicken manure rates especially at (2g urea and 200g chicken manure) led to significant increase most of the studied parameters. The interaction between urea with chicken manure at high rates resulted in the highest values of number of runners (17 Plant-1), length of runner (125.67 cm), number of seedlings (5.33 Runner-1), number of seedlings (35.33 Plant-1), dry weight of vegetative growth (26.60 g. plant-1), the total nitrogen in leaves (3.79 %), phosphorus (0.83 %) and potassium (1.80 %)